Mean-Field Model Beyond Boltzmann-Enskog Picture for Dense Gases (Communications in Computational Physics, 2020)
This work proposes an extension to Boltzmann BGK equation for densegases. The present model has an H-theorem and it allows choice of the Prandtl numberas an independent parameter. I show that similar to Enskog equation this equation canreproduce dynamics of dense gases.